Molecular Mechanisms of Alzheimer’s Disease Induced by Amyloid-β and Tau Phosphorylation Along with RhoA Activity: Perspective of RhoA/Rho-Associated Protein Kinase Inhibitors for Neuronal Therapy - Eun Hee Ahn; Jae-Bong Park (Cells)
Amyloid-β peptide (Aβ) is a critical cause of Alzheimer’s disease (AD). It is generated from amyloid precursor protein (APP) through cleavages by β-secretase and γ-secretase. γ-Secretase, which includes presenilin, is regulated by several stimuli. Tau protein has also been identified as a significant factor in AD. In particular, Tau phosphorylation is crucial for neuronal impairment, as phosphorylated Tau detaches from microtubules, leading to the formation of neurofibrillary tangles and the destabilization of the microtubule structure. This instability in microtubules damages axons and dendrites, resulting in neuronal impairment. Notably, Aβ is linked to Tau phosphorylation. Another crucial factor in AD is neuroinflammation, primarily occurring in the microglia. Microglia possess several receptors that bind with Aβ, triggering the expression and release of an inflammatory factor, although their main physiological function is to phagocytose debris and pathogens in the brain. NF-κB activation plays a major role in neuroinflammation. Additionally, the production of reactive oxygen species (ROS) in the microglia contributes to this neuroinflammation. In microglia, superoxide is produced through NADPH oxidase, specifically NOX2. Rho GTPases play an essential role in regulating various cellular processes, including cytoskeletal rearrangement, morphology changes, migration, and transcription. The typical function of Rho GTPases involves regulating actin filament formation. Neurons, with their complex processes and synapse connections, rely on cytoskeletal dynamics for structural support. Other brain cells, such as astrocytes, microglia, and oligodendrocytes, also depend on specific cytoskeletal structures to maintain their unique cellular architectures. Thus, the aberrant regulation of Rho GTPases activity can disrupt actin filaments, leading to altered cell morphology, including changes in neuronal processes and synapses, and potentially contributing to brain diseases such as AD.